Free radical scavenging and anti-isolated human LDL oxidation activities of Butea superba Roxb. extract - Kittipot Sirichaiwetchakoon; Griangsak Eumkeb (BMC, 2024)
Abstract Background Butea superba Roxb. (B. superba), is an herbal plant traditionally used for rejuvenation. Additionally, there have been reports on its antioxidant properties. Low-density lipoproteins (LDL) oxidation is the leading cause of cardiovascular diseases (CVDs). Natural products with antioxidant properties have the potential to inhibit LDL oxidation. However, no work has been done about the anti-isolated human LDL oxidation of B. superba extract (BSE). This study aimed to investigate the antioxidant potential of BSE and its ability to prevent isolated human (LDL) oxidation induced by free radical agents. Methods The antioxidant properties were investigated by antioxidant assays, including 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-azinobis-(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS), ferric reducing ability power (FRAP), nitric oxide (NO) and peroxynitrite scavenging assay. More so, anti-isolated human LDL oxidation activities were evaluated by 2,2'-azobis (2-amidinopropane) dihydrochloride (AAPH) and 3-morpholinosydnonimine hydrochloride (SIN-1) induced LDL oxidation assay. Results BSE exhibited a significant (p < 0.05) antioxidant activity in all the test systems, demonstrating its potential as a potent free radical scavenger. It displayed scavenging effects on DPPH (p < 0.05; IC50 = 487.67 ± 21.94 µg/ml), ABTS (p < 0.05; IC50 = 30.83 ± 1.29 µg/ml). Furthermore, it generated significantly (p < 0.05) increased antioxidant capacity in a dose-dependent manner in FRAP assay and exhibited significantly (p < 0.01) higher percent NO scavenging activity than gallic acid. Besides, BSE at 62.5 µg/ml exhibited a considerable percent peroxynitrite scavenging of 71.40 ± 6.59% after a 2 h period. Moreover, BSE demonstrated anti-isolated human LDL oxidation activity induced by AAPH and SIN-1 (p < 0.05) and revealed scavenging activity similar to ascorbic acid (p > 0.05). Identifying the main constituents of BSE revealed the presence of genistein, daidzein, and biochanin A through Liquid Chromatography-Mass Spectrometer/Mass Spectrometer (LC-MS/MS) analysis. Conclusion This is the first report that the presence of isoflavones in BSE could play an important role in its antioxidation and isolated human LDL oxidation scavenging properties. These findings suggest the potential for developing antioxidant herbal supplements. However, further studies must be investigated, including efficacious and safe human dosages.